2021
DOI: 10.1007/s11033-020-06075-1
|View full text |Cite
|
Sign up to set email alerts
|

Tissue micro-RNAs associated with colorectal cancer prognosis: a systematic review

Abstract: Colorectal cancer (CRC) is a multifactorial disease commonly diagnosed worldwide, with high mortality rates. Several studies demonstrate important associations between differential expression of micro-RNAs (miRs) and the prognosis of CRC. However, only a few systematic reviews emphasize the most relevant miRs able to contribute to the establishment of new prognostic biomarkers in CRC patients. The present study aimed to identify differentially expressed tissue miRs associated with prognostic factors in CRC pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 154 publications
0
11
0
Order By: Relevance
“…miR-4798-3p presents negative results only among males; however, the mechanisms of interaction of this miRNA with AF are still unknown, and further studies are needed to elucidate these mechanisms. miR-20a-5p has already been reported as a biomarker of other diseases, such as non-small-cell lung cancer, which mainly inhibits neoplastic cell proliferation [ 11 , 30 ]. Therefore, these miRNAs are potential biomarkers, and further studies are required to clarify their roles in the development of AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-4798-3p presents negative results only among males; however, the mechanisms of interaction of this miRNA with AF are still unknown, and further studies are needed to elucidate these mechanisms. miR-20a-5p has already been reported as a biomarker of other diseases, such as non-small-cell lung cancer, which mainly inhibits neoplastic cell proliferation [ 11 , 30 ]. Therefore, these miRNAs are potential biomarkers, and further studies are required to clarify their roles in the development of AF.…”
Section: Discussionmentioning
confidence: 99%
“…In association with mature miR and other proteins, the Argonaut proteins constitute the RNA-induced silencing complex, which targets specific mRNAs. After binding to mRNAs, GW182/TNRC6 proteins interact with Argonaut proteins and recruit the CCR4-NOT deadenylase complex, which induces the degradation or silencing of mRNAs [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…miR-20a-5p has already been reported as a biomarker of other diseases, such as non-small cell lung cancer, which mainly inhibits neoplastic cell proliferation [11,30]. Therefore, these miRNAs are potential biomarkers, and further studies are required to clarify their roles in the development of AF.…”
Section: Discussionmentioning
confidence: 99%
“…In association with mature miR and other proteins, the Argonaut proteins constitute the RNA-induced silencing complex, which targets speci c mRNAs. After binding to mRNAs, GW182/TNRC6 proteins interact with Argonaut proteins and recruit the CCR4-NOT deadenylase complex, which induces the degradation or silencing of mRNAs [9][10][11].…”
mentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small noncoding RNAs 18-25 nucleotides in length that function by regulating target genes. Studies have demonstrated that the differential expression of miRNAs has an important relationship with the occurrence, development and prognosis of CRC (10)(11)(12). LncRNAs act as sponges/competing endogenous RNAs (ceRNAs) to regulate the post-transcriptional regulation of miRNAs and are factors in the etiology of numerous diseases (12).…”
Section: Introductionmentioning
confidence: 99%